2015
DOI: 10.1080/14786419.2015.1030341
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and antibacterial activity of extracts obtained from the inflorescences of Cirsium canum (L.) all

Abstract: The aim of this study was to investigate phenolic acids and flavonoids in methanolic, dichloromethane, acetone and ethyl acetate extracts and fractions from inflorescences of Cirsium canum (L.). RP-HPLC analysis enabled identification of the following: chlorogenic acid, caffeic acid, p-coumaric acid, protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, syringic acid, trans-cinnamic acid, luteolin-7-glucoside, apigenin-7-glucoside, kaempferol-3-glucoside, linarin, apigenin, rutoside, luteolin and kaempfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…It has been observed that many plants contain different substances with antimicrobial activities, which can serve as a source and template for the synthesis of new antimicrobial drugs. (19,21) The knowledge about the therapeutic possibility of using both extracts and isolated phytochemicals from Marrubium spp. has become more popular as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that many plants contain different substances with antimicrobial activities, which can serve as a source and template for the synthesis of new antimicrobial drugs. (19,21) The knowledge about the therapeutic possibility of using both extracts and isolated phytochemicals from Marrubium spp. has become more popular as well.…”
Section: Resultsmentioning
confidence: 99%
“…All the experiments were performed three times similarly to the previously described procedures. (17)(18)(19).…”
Section: Microbiological Assaymentioning
confidence: 99%
“…This family of compounds has been previously tested to determine their utility as antimicrobial agents [24]. Ferulic, vanillic, chlorogenic and p -coumaric acid were also detected in the chromatogram and then identified by their individual spectra [25]; both the latter two acids have demonstrated an antimicrobial effect against some Gram Positive and Gram Negative bacteria [26,27,28]. On the other hand, evidence of small quantities of terpenes, such as saponins, was also found in the chromatographs and spectra; it is also documented that these phytocompounds have important antimicrobial activity [29].…”
Section: Resultsmentioning
confidence: 99%
“…More than three billion people worldwide have been affected by this deadly disease (Verlinden, Louw, Birkholtz, 2016). The increasing resistance of malarial parasites to available drugs is a major reason for these large statistics, despite many reports on the antimalarial efficacy of flavonoids (Friedman, 2007;Kozyra et al, 2015). The development of novel antimicrobial drugs is still in demand owing to increasing incidence of infection caused by the rapid development of microbial resistance to most known antibiotics.…”
Section: Introductionmentioning
confidence: 99%